Придуманные имена: (рассказы о псевдонимах) / В.Г. Дмитриев - Дмитриев Валентин Григорьевич (Современник, 1986)
Экземпляры: ф. 9 (20210818) / Инвентарный номер: 28504 / Цена: 10.00 / Сис.шифр: 83.3(0) / Авт.знак: Д53 / ГРНТИ: 17.09.09 / ББК: 83.3(0)